Proceedings of the Twenty-Fifth Annual Symposium on Computational Geometry 2009
DOI: 10.1145/1542362.1542404
|View full text |Cite
|
Sign up to set email alerts
|

Parallel geometric algorithms for multi-core computers

Abstract: Computers with multiple processor cores using shared memory are now ubiquitous. In this paper, we present several parallel geometric algorithms that specifically target this environment, with the goal of exploiting the additional computing power. The algorithms we describe are (a) 2-/3-dimensional spatial sorting of points, as is typically used for preprocessing before using incremental algorithms, (b) d-dimensional axis-aligned box intersection computation, and finally (c) 3D bulk insertion of points into Del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 27 publications
(20 reference statements)
0
27
0
Order By: Relevance
“…Parallel incremental insertion algorithms are generally bootstrapped with a sequentially obtained initial triangulation of a subset of the input points. Subsequently, the rest of the points can be inserted in parallel by identifying the surrounding simplex for each point, removing it and re-triangulating the resulting cavity with the inserted point and the facets of the surrounding simplices [2,7,15]. The Delaunay property of the re-triangulated region is ensured by performing local flips [14,15].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Parallel incremental insertion algorithms are generally bootstrapped with a sequentially obtained initial triangulation of a subset of the input points. Subsequently, the rest of the points can be inserted in parallel by identifying the surrounding simplex for each point, removing it and re-triangulating the resulting cavity with the inserted point and the facets of the surrounding simplices [2,7,15]. The Delaunay property of the re-triangulated region is ensured by performing local flips [14,15].…”
Section: Related Workmentioning
confidence: 99%
“…To avoid simultaneous access to the same simplex during re-triangulation, locks need to be employed. Various locking strategies are studied in [2,15]. The algorithm of Batista et al is the basis for the parallel DT algorithm found in the CGAL library [12].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Amato and Preparata (1993); Cignoni et al (1998); Zhou et al (2001); Batista et al (2010). Typically, such algorithms divide the point set up into several smaller subsets, each of which can then be triangulated independently from the others.…”
Section: Parallel Algorithm For Delaunay Tessellation Constructionmentioning
confidence: 99%